Greater insulin response to acute fructose ingestion among Māori and Pacific people compared to European people living in Aotearoa New Zealand. Issue 2 (12th February 2019) - Murphy, Rinki; Gamble, Greg D.; House, Meaghan; Pool, Bregina; Horne, Anne; Merriman, Tony R.; Dalbeth, Nicola
Abstract: Background: Fructose consumption has been linked with insulin resistance, obesity and diabetes, which are more prevalent in those of Māori or Pacific ethnicity compared to New Zealand European. Aim: To determine whether the acute effects of fructose consumption on serum glucose, insulin, lipids and C‐reactive protein differs according to body mass index (BMI) and/or ethnicity. Methods: Participants of Māori ( n = 25), Pacific ( n = 26) or New Zealand European ( n = 25) ethnicity consumed a 64 g fructose/16 g glucose solution. Changes in lipids, glucose, insulin and C‐reactive protein were analysed using mixed models for repeated measures. Results: After adjustment for age and gender, those with higher BMI had a higher glucose ( P = 0.0064) and insulin ( P = 0.0007) response than those with lower BMI. Those of Māori or Pacific ethnicity had similar glucose levels ( P = 0.077) to those of New Zealand European ethnicity but higher insulin responses ( P = 0.0005), which remained after additional adjustment for BMI ( P = 0.001). Reported sugar‐sweetened beverages (SSB) intake was higher among Māori and Pacific than New Zealand European (median 1.0 vs 0.0 SSB/day P = 0.002). Conclusion: Even after adjustment for BMI, those of Māori and Pacific ethnicity have a significantly higher insulin response to fructose than New Zealand Europeans. Higher habitual SSB intake may be a contributing factor.